Laughter as a specific means of physical recreation - Lucie Lauermanová; Dana Štěrbová; Martin Kudláček (Palacký University Olomouc, 2014)
BACKGROUND: Laughter, the accompanying phenomenon of human society in the course of its historical development, is not just a physical manifestation of hilarity. Laughter acts as the main means of activities built on the positive eﬀects of laughter on man and on his health. This includes laughter yoga and laughter therapy. OBJECTIVE: The aim of this paper is to critically evaluate and summarize the literature, and to develop an expert compilation of laughter, its eﬀects and applications, and to assess laughter as a specific means of physical recreation. In addition, this paper was to provide a basic insight into the issue of the importance of laughter in the context of physical recreation, to highlight the potential of the topic and bring it to professionals and to the general public. METHOD: The basic method was a secondary analysis of data. I used various keywords and identified criteria for inclusion and exclusion. To assess laughter as a specific means of physical recreation was used as a thematic analysis of the data. RESULTS: Laughter meets the basic attributes specified for the means of physical recreation, because there is a consensus between the eﬀects of laughter and the aims of physical recreation. CONCLUSIONS: In light of the physical recreation we see potential in the use of laughter as a specific means of physical recreation. The paper presents theoretical material for discussion and further research in this or a similar topic.